Business in a changing society : festschrift for Peter Brabeck-Letmathe - Brabeck-Letmathe, Peter, 1944-; Koopmann, Andreas (Zurich : Neue Zürcher Zeitung Publishing, 2014)
"On the occasion of Peter Brabeck-Letmathe's 70th birthday a group of his friends invited 31 authors to contribute to this festschrift, honoring his great achievements in providing business leadership and contributing to public dialogue on important issues. Leaders from politics, academia, civil society and business who know Peter Brabeck draw a fascinating, multifaceted picture of the quality, speed and nature of the ongoing and often accelerating change taking place in society, technology and markets. It is a change that is not only relevant for him as chairman of Nestlé, but also for citizens and businesses around the world today, and in years to come"--
I. Major global shifts and their drivers -- II. Corporate change-business in society -- III. On the power of ideas -- IV. Civil society-actor and partner -- V. Changes and challenges ion global nutrition and health -- VI. The water challenge-need for partnerships -- Vii. Policy responses to global shifts and challenges.
Includes bibliographical references.
Keywords: Brabeck-Letmathe, Peter, -- (1944- ); Brabeck-Letmathe, Peter -- Mélanges et hommages; Nestlé SA; Industries -- Social aspects; Organizational change; Οργανωτική αλλαγή -- Διοίκηση και οργάνωση.; Παγκοσμιοποίηση.; Cooperation; Business networks; Globalization; Festschriften; Business networks; Cooperation; Festschriften; Globalization; Industries -- Social aspects; Organizational change